1960
DOI: 10.2134/agronj1960.00021962005200050001x
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Precipitation, Temperature, and the Yield of Soybeans on the Agronomy South Farm, Urbana, Illinois1

Abstract: Synopsis Precipitation and maximum daily temperatures from June 25 through September 20 explained 68% of the variation in soybean yields from 1909 through 1957. Above‐normal precipitation during July (period of major vegetative growth) and from mid‐August to mid‐September (grain filling period) increased soybean yields, but abundant rainfall during other periods decreased yields. Maximum temperatures during July and August are too high for optimum soybean yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
2

Year Published

1972
1972
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 2 publications
3
20
0
2
Order By: Relevance
“…Numerous studies have been conducted on effects of day length, light saturation (Bohning and Burnside 1956;Sakamoto and shaw 1967),-air temperature (Howell andcartter 1953, 1958), moisture supply of selected growth periods (Runge and odell 1960), and nutritional levels (ohtrogge 1960): soil temperatures have been compared under greenhouse conditions (Earley and Cartter 1945) atd between geographical regions (viljoen 1937; weiss et al 1952). rn a comprehensive analysis of fleld trials at one location over a number of vears.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted on effects of day length, light saturation (Bohning and Burnside 1956;Sakamoto and shaw 1967),-air temperature (Howell andcartter 1953, 1958), moisture supply of selected growth periods (Runge and odell 1960), and nutritional levels (ohtrogge 1960): soil temperatures have been compared under greenhouse conditions (Earley and Cartter 1945) atd between geographical regions (viljoen 1937; weiss et al 1952). rn a comprehensive analysis of fleld trials at one location over a number of vears.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean seed yield is more affected by water stress during the flowering-pod setting period (Runge and Odell, 1960; Thompson, 1970;Ashley and Ethridge, 1978;Korte et al, 1983a;Kadhem et al, 1985a) and the seed filling period (Doss et al, 1974;Constable and Hearn, 1978;Brown et al, 1985;Griffin et al, 1985) than during the vegetative period.…”
mentioning
confidence: 99%
“…Conversely, above-normal temperatures from June 14 to September 20, and especially during anthesis, caused decreased yields. Runge and Odell (1958) found similar results for soybean yields. According to Frey and Browning (1959) Temperature affects other plant processes also.…”
Section: Temperature and Crop Yieldssupporting
confidence: 66%
“…Likewise, the number of heat units required for a variety to reach maturity was similar from year to year and early-maturing varieties-required fewer heat units than late-maturing ones. Using data from the long-time Illinois corn tests , Runge and Odell (1960) showed that above-normal temperature during May 20 r_ June 13 (first three weeks after planting) increased grain yields. Conversely, above-normal temperatures from June 14 to September 20, and especially during anthesis, caused decreased yields.…”
Section: Temperature and Crop Yieldsmentioning
confidence: 99%